Linear enamel hypoplasia in large-bodied mammals of Pleistocene northern Vietnam, with a special focus on Pongo. (20th October 2020) - Bacon, Anne-Marie; Antoine, Pierre-Olivier; Nguyen, Thi Mai Huong; Westaway, Kira; Zhao, Jian-xin; Nguyen, Anh Tuan; Duringer, Philippe; Ponche, Jean-Luc; Sam, Canh Dung; Truong, Huu Nghia; Tran, Thi Minh; Nguyen, Thi Kim Thuy; et al.
Abstract: The Coc Muoi fauna provides a good example of the type of tropical mammalian communities that existed in northern Vietnam during the late Middle Pleistocene. The first results of the analysis of hypoplasia indicated that rhinoceroses and wild cattle were exposed to multiple physiological and psychological stress events specific to age [Bacon et al., 2018. A rhinocerotid-dominated megafauna at the MIS 6-5 transition: The late Middle Pleistocene Coc Muoi assemblage, Lang Son province, Vietnam. Quat. Sci. Rev. 186, 123–141]. In this paper, we aim to supplement the study of hypoplasia in the orangutans ( Pongo ) from Coc Muoi and, more widely, from different Pleistocene faunas. To address this issue, we conducted a macroscopic analysis of linear enamel hypoplasia [LEH] on Pongo from three collections: Coc Muoi (148–117 ka), Duoi U'Oi (70–60 ka), and Tham Khuyen (>475 ka). Such comparative analysis based on isolated teeth is constrained by numerous biases including: the small datasets; the differential representation of tooth types; the difficulty in distinguishing first from second molars; the small number of individuals [MNI]; the differential representation of males versus females. The data analysis has been divided into two parts: (1) an analysis of the frequency and expression of LEH on incisors, premolars, and molars (three sites), and (2) an analysis of the frequency and expression of LEH on a set of canines (Tham Khuyen). We used a reference sample composed of 17 adult and 10 immature Pongo individuals to determine the age range of fossil Pongo individuals, at the time of the defects. Results show that hypoplasia was a common phenomenon in Pleistocene Pongo : two individuals at Coc Muoi; 2 out of 3 individuals at Duoi U'Oi; and 4 out of 6 individuals at Tham Khuyen. They experienced multiple stresses between ~2 and 5 years of age, a period of great vulnerability for immature individuals. The occurrence of accentuated lines of hypoplasia on canine crowns of Tham Khuyen suggests a greater intensity of the stressor, in a time range consistent with the long dietary and behavioral transition of the weaning. In terms of paleoecology, Pleistocene orangutans from the Asian mainland could survive in different environmental conditions than those they occupy today. Various sources (archaeozoology, geological context, and ecology of wild populations), suggest that they might have been larger apes than extant orangutans, living in limestone forests on hills and tower karsts.